PEMBERDAYAAN MASYARAKAT PESISIR KELOMPOK NELAYAN PENGOLAH IKAN DI KECAMATAN BACUKIKI KOTA PARE-PARE, PROPINSI SULAWESI SELATAN - Harlina, Harlina; Auliyah, Andi Nur (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, 2023)
The Science and Technology Program for the community (PKM) has been carried out in Bacukiki Kora Parepare District, South Sulawesi Province with 2 groups of partners processing fishery products This activity is carried out by transferring technology for making shredded tuna which is still traditional to be more modern and hygienic. In addition, training and assistance were carried out to diversify processed anchovy products into various kinds of processed products such as rempeyek anchovies, balado seasoned anchovies and anchovy spicy sambel with vacuum packaging techniques to make it more hygienic as well as business management training activities. The method used in the training is the participatory method, which involves as many partners as possible in lectures, discussions, and practices. The training program that has been agreed with business group partners is the diversification of processed anchovy and tuna fish pabon products, the design of making product packaging. Business management training. covering finance and marketing strategies. The results of this activity show that the transfer of technology for making more modern tuna shredded products was accepted by the partner group because the procedure was easier, the results were more satisfactory and developed into a household-scale industry. In addition, partner groups have been able to produce processed anchovy products made from local anchovies.